Earthquake forecasting model for Nepal to improve prevention - Sathian, Brijesh; van Teijlingen, Edwin R (Nepal Journal of Epidemiology, 2018)
There is an urgent need of earthquake forecasting model for Nepal in this current scenario. It can be developed by the scientists of Nepal with the help of experienced international scientists. This will help the Nepalese to take timely and necessary precautions. We would argue that above all we need to use earthquake prediction knowledge to improve the disaster prepardness in local communities, service providers (hospitals, Non-Governmental Organizations, police, etc.), government policy-makers and international agencies. On the whole, both seismology and public health are most successful when focusing on prevention not on prediction per se. J Epidemiol. 2017;7(4); 700-701.